2007
DOI: 10.1359/jbmr.061117
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Deletion of Exon 3 of the Androgen Receptor Gene Results in Trabecular Bone Loss in Adult Male Mice

Abstract: The mechanism of androgen action on bone was studied in male mice with the AR deleted in mature osteoblasts. These mice had decreased trabecular bone volume associated with a decrease in trabecular number, suggesting that androgens may act directly on osteoblasts to maintain trabecular bone.Introduction: Androgens modulate bone cell activity and are important for the maintenance of bone mass. However, the mechanisms by which they exert these actions on bone remain poorly defined. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
106
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 64 publications
(127 reference statements)
15
106
1
1
Order By: Relevance
“…(27) Our findings suggest that this age-related decline in trabecular integrity is enhanced by inactivation of the AR in osteocytes, in line with results from previous mice models. (12,13) Studies using the col2.3Cre AR-knockout mice and osteocalcin Cre ARknockout mice also demonstrated that an inactivation of the DNA binding-dependent functions of the AR, specifically in mature osteoblasts of male mice, increases bone resorption and reduces structural integrity of the bone, leading to a similar acceleration of the age-related reduction in trabecular bone volume. (12,13) Expanding the findings of these studies, our current data support the concept that, for the maintenance of the trabecular network after puberty, a functional AR is not only required at the osteoblast stage but also at the osteocyte stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(27) Our findings suggest that this age-related decline in trabecular integrity is enhanced by inactivation of the AR in osteocytes, in line with results from previous mice models. (12,13) Studies using the col2.3Cre AR-knockout mice and osteocalcin Cre ARknockout mice also demonstrated that an inactivation of the DNA binding-dependent functions of the AR, specifically in mature osteoblasts of male mice, increases bone resorption and reduces structural integrity of the bone, leading to a similar acceleration of the age-related reduction in trabecular bone volume. (12,13) Expanding the findings of these studies, our current data support the concept that, for the maintenance of the trabecular network after puberty, a functional AR is not only required at the osteoblast stage but also at the osteocyte stage.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, previous models inactivating the AR at earlier stages of the osteoblast did not observe a significant difference in cortical structure, but mechanical properties were not documented. (12,13) The absence of a major cortical phenotype across a number of similar mice models contrasts with the significant cortical phenotype characterized by reduction of periosteal expansion observed in the ubiquitous ARKO model. (5) Puberty appears to be a critical period for the development of skeletal sexual dimorphism as characterized by wider and longer bones in male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some results have indicated a reduction in cortical bone thickness but no change in periosteal circumference when the osteocalcin promoter was used to target the exon 3 of the AR gene, 19 whereas no effect on the cortical bone was observed in another study utilizing the type I collagen 2.3 promoter. 20 In a recent study by Sinnesael et al, 21 osteocytic AR was shown to be crucial for the maintenance of trabecular bone volume in male mice. The role of AR in the regulation of the female skeleton is currently incompletely characterized.…”
Section: Introductionmentioning
confidence: 97%
“…Inactivation of the AR DNA-binding activity in osteocalcinexpressing cells 19 and in collagen-1-synthesizing osteoblasts 20 has been shown to reduce trabecular bone volume in male mice. In cortical bone various effects have been reported.…”
Section: Introductionmentioning
confidence: 99%